Problem-Solving Ability of Science Students in Optical Wave Courses (Jurnal Pendidikan IPA Indonesia, 2017)
Optical wave courses at the Department of Science discuss waves and optics. The purpose of this study is to describe the problem-solving ability of students in optical wave courses. The method used is quantitative descriptive with one group pre-test post-test design. Method of data collection involves a test given to students before and after the student worksheet was provided in the course of optical waves. This study showed an increase in scores experienced by as many as 15 students. This shows that the problem-solving ability of students has increased.